Proposições geométricas com animações - Mendes, Ijosiel [UNESP] (2014)
The present work aims at presenting animations in GeoGebra to introduce propositions of plane Euclidean geometry as a model for math teachers, as well as submit a proposal for how to use them as a tool for development on the part of teachers, the learning situations students to be applied in the computer room. Such situations have an investigative nature, so that the students themselves conjecture geometrical propositions after executing commands resulting from the animations. These propositions have been selected in order to facilitate the resolution of a problem, which is related to determining the center of a circle. The first results with the state school teachers show that the alternative of animations in GeoGebra for teaching geometry is promising